IMPLEMENTATION IMPACT OF INTEGRATIVE THEMATIC LEARNING FOR DEVELOPING THE STUDENT AND TEACHER’S COMPETENCIES IN THE ISLAMIC ELEMENTARY SCHOOL (MADRASAH IBTIDAIYAH) IN YOGYAKARTA SPECIAL REGION - Sukiman Hakim (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2017)
This article is the result of qualitative research conducted in five State Islamic Elementary Schools (MIN) in Yogyakarta Special Region. This article is aimed to elaborate critically the impact of integrative thematic learning implementation for the development of competencies of learners and teachers. The findings in this paper are: first, the implementation of integrative thematic learning at The State Islamic Elementary School (MIN) has a positive impact for the development of students' critical and creative attitude and critical thinking skill. The weakness of this research result is that the mastery of learners on the concept/subject matter is still poor. Second, the implementation of integrative thematic learning at State Islamic Elementary School (MIN) has a positive impact on teacher competence improvement, namely: (1) encouraging teachers to keep learning well related to integrative thematic learning concepts, learning materials, learning models, learning strategies / methods, media development and sources learning, and assessment;(2) encouraging teachers to prepare for more mature learning; and (3) encourage teachers to further enhance cooperation with peers and parents/ guardians of learners.